Short circuit analysis in the marine L.V. A.C power systems:an essential aspect of shipbuilding industry - Us, Mustafa Atilla (Graduate School, 2023)
Short circuits in ship electrical systems can cause equipment failure, fires, and even death. As thus, short circuit analysis is an important component of ship design and maintenance. This thesis examines the importance of short circuit analysis in the shipbuilding industry, the problems it presents, and the strategies available for overcoming these hurdles. The thesis begins by discussing the various implications of short circuits, such as equipment damage, power outages, and safety risks. The basic principles of short circuit analysis are then explained, including fault current calculations, fault isolation, and protective equipment coordination. Following that, the thesis discusses the difficulties associated with short circuit analysis in the shipbuilding industry, such as the complex and large-scale nature of ship electrical systems, the difficulty of obtaining testing equipment, and the requirement for specialized tools and expertise. The study recommends a strategy to solve these issues, including the use of modern simulation tools for fault diagnosis, the establishment of standard operating procedures for testing and maintenance, and the training of ship employees in short circuit analysis and prevention. The importance of classification organizations, which create standards and give direction on short circuit analysis and prevention, is also discussed in the thesis. It underlines the need of collaboration with classification bodies in ensuring that ships satisfy safety and regulatory criteria. The paper ends by emphasizing the significance of short circuit analysis in the shipbuilding sector. It shows why this study is crucial for assuring the safety and dependability of shipboard electrical systems. In addition, the paper underlines the need of shipbuilders having a thorough grasp of short circuit analysis and its application in order to assure the safety and reliability of their boats. In closing, the study presents a thorough review of short circuit analysis in the shipbuilding industry, including its significance, process, advantages, and application. It is a valuable reference for shipbuilders and electrical engineers involved in ship design and construction. Shipbuilding processes typically take months, and sometimes even years, to complete. Therefore, it is crucial for the electrical design to progress in harmony with the ship's equipment, considering cost and tracking aspects. However, critical design milestones must be achieved for the project to commence. At this point, conducting accurate and timely short circuit calculations becomes vital. Even in cases where the necessary information for short circuit analysis is unavailable, the aim is to calculate the maximum short circuit current with minimal errors, thanks to industry standards published for the shipbuilding sector. Various strategies and measures will be researched and examined to minimize errors. In this way, project progress can continue without interruptions, and the electrical design can seamlessly integrate into the shipbuilding process. During this process, electrical system integrators take on significant responsibilities, ensuring the proper integration of electrical equipment on board and the smooth operation of all electrical products. They facilitate the correct integration of electrical equipment, as well as the balanced distribution of electrical loads. Finally, short circuit analysis is an important phase in the electrical design, safety, and dependability of a ship while it is being built. Although it presents difficulties in the shipbuilding industry, there are solutions available to overcome these difficulties and ensure that ships are designed, built, and maintained to the highest safety standards. In addition, the impact of power sources and electrical consumers on the maximum short circuit will be emphasized. Furthermore, the study explains how to perform calculations with insufficient consumer and generator information at the beginning of the project, and when and how these calculations should be updated through iterative methods. This study aims to contribute to the understanding of the factors necessary for accurate and reliable results in short circuit analysis. Within the scope of this study, 11 different types of vessels will be examined, including Fast Crew Suppliers, Motor Yachts, Tugboats, Cruise Vessels, Factory Longliners, Oil Spill Response Vessels, Freezer Trawlers, Trailing Suction Hopper Dredgers, Oil Tankers, Ro-Ro Vessels, and General Cargo Vessels. Various conclusions will be drawn using the data obtained from these vessel types. The objective of this study is to analyse the electrical loads and generator information of different vessel types and derive various insights based on this data.
Gemi inşa endüstrisinin önemli bileşeni: Alternatif akım düşük gerilim güç sistemlerinde kısa devre analizi
Thesis (M.Sc.) -- Istanbul Technical University, Graduate School, 2023
Keywords: hip electrical systems; ship design; short circuit analysis